Mutazilah : Diantara Kebebasan Berfikir Dan Kehendak Tuhan - Muhammad Zaky Dhiyaul Haq; Billy Ramadhan; Dini Amalia Salsabila; Salsa Sabila Firmansyah; Najwa Azahra; Muhamad Parhan (Pusat Riset dan Inovasi Nasional, 2024)
This article discusses the development and views of the Mutazilah, a school of Islam that emphasizes human freedom of thought while limiting God's absolute will. History and divisions within the Islamic community provide an important context for understanding the teachings of the Mutazilah, especially regarding the concepts of tawhid, divine justice, God's promises and threats, man's position between two extremes, as well as the encouragement to do good and the prohibition against wrongdoing. Using a qualitative approach and literature review, this study analyzes primary and secondary sources related to the Mutazilah. The findings highlight the view that they emphasize human freedom of thought as the key to interpreting religious texts, with the belief that humans have the freedom to determine their actions.This article explores the main tenets of the Mutazilahs. A thorough understanding of the Mutazilah's contribution to Islamic theological history provides valuable insights into the complexity of ideas and views within the religion. In conclusion, this article makes an important contribution to exploring the diversity of Islamic theological thought through the lens of the Mutazilah.